The US volunteers in the Southern Philippines counterinsurgency, pacification, and collaboration, 1899-1901 - Reed, John Scott (2020)
"The U.S. Volunteers who served in the Philippines from 1899 to 1901 enlisted fully understanding they would fight a colonial war. The Regular Army of 1899 had yet to recover from its Spanish War combat and disease losses, and their country needed an additional force to pacify the Philippines. Acting out of a sense of reflexively patriotic masculine obligation, and a profound belief in the self-evident superiority of American institutions, the USVs were tasked to impose their nation's will on a non-Western population, and they were willing to endure severe physical hardships and lethal risks in the service of that effort. Burden and Honor examines the combat and garrison life of volunteer soldiers on four islands in the Southern Philippines: Samar, Leyte, Panay, and Northern Mindanao, and their central role within a pacification strategy that combined military operations with martial law coercion to exhaust guerrilla bands and suppress elite support for continued resistance. Reed concludes that the success of the US counterinsurgency campaign was a result of a realistic pacification strategy implemented by sound operational decisions, the discipline and tactical skills of the US Volunteer force, and a vastly improved Army medical system."--